Ultrafine microstructure and hardness in Fe-Cr-Co alloy induced by spinodal decomposition under magnetic field. (1st February 2021) - Xiang, Zhaolong; Zhang, Lin; Xin, Yan; An, Bailing; Niu, Rongmei; Mardani, Masoud; Siegrist, Theo; Lu, Jun; Goddard, Robert E.; Man, Tiannan; Wang, Engang; Han, Ke
Abstract: Application of an external magnetic field during heat treatment affects the hardness of magnetic Fe-Cr-Co alloys. The microstructure and composition at atomic scale, as well as the hardening mechanisms need extensive studies. Using atomic resolution STEM, we investigated the effect of a 3 T magnetic field on the spinodal decomposition, as well as microstructure and hardness in step-aged Fe27wt. %Cr15wt. %Co samples. Spinodal decomposition resulted in a homogeneous α phase transforming into an Fe-Co rich α1 phase and a Cr rich α2 phase. Although α1 and α2 showed distinct contrast at low magnification Z -contrast images, close examination at atomic scale of the samples showed no sharp α1 /α2 interfaces. Inside each phase, composition fluctuations occurred. A 3 T external magnetic field during step aging increased the size of the α1 phase and introduced microstructural anisotropy, which is desired for permanent magnet applications, In addition, the spinodal decomposition increased the hardness. Annealing in a 3 T magnetic field decreased the hardness but increased the ductility, which is desirable for manufacturing permanent magnets. The change in hardness values is attributed to the composition fluctuations of Fe, Cr and Co, and we further discuss the mechanisms for composition fluctuations and hardness. Graphical abstract: Unlabelled Image Highlights: Variation of both microstructure and composition induced by spinodal composition was smooth at atomic scale. Magnetic field increased both amplitude and wave-length of spinodal composition. Magnetic field elongated α1 domains lined up parallel to the direction of the magnetic field. Increased wave-length of spinodal composition resulted in decreased hardness and increased toughness. Mechanisms for fluctuations of composition and hardness were controlled by diffusion of certain alloying elements.